2016
DOI: 10.1016/j.bonr.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The associations of exposure to combined hormonal contraceptive use on bone mineral content and areal bone mineral density accrual from adolescence to young adulthood: A longitudinal study

Abstract: BackgroundThe association of long term combined hormone based contraceptives (CHC) use on bone mineral content (BMC) and areal bone mineral density (aBMD) development remains controversial, as it appears that the relationship may be age-dependent. The purpose of this study was to investigate the long-term associations of CHC exposure on the accrual of bone parameters from adolescence into young-adulthood.Methods110 women (67 exposed to CHC) were drawn from the Pediatric Bone Mineral Accrual Study (PBMAS). Seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
1
18
1
1
Order By: Relevance
“…In view of this epidemiological situation, the identification of factors associated with bone health is fundamental to combat the progression of osteometabolic diseases. In this sense, studies have shown that age and gender (5)(6)(8)(9)(10) , use of medications and hormones (11)(12) , body composition (6)(7)(8)(9)(10) , behavioral and environmental aspects (13)(14) , and food consumption (15) are factors associated with bone metabolism. However, few studies have been conducted with adults of both genders (4,16) , and the existing studies assess risk factors in isolation (5,15) .…”
Section: Introductionmentioning
confidence: 99%
“…In view of this epidemiological situation, the identification of factors associated with bone health is fundamental to combat the progression of osteometabolic diseases. In this sense, studies have shown that age and gender (5)(6)(8)(9)(10) , use of medications and hormones (11)(12) , body composition (6)(7)(8)(9)(10) , behavioral and environmental aspects (13)(14) , and food consumption (15) are factors associated with bone metabolism. However, few studies have been conducted with adults of both genders (4,16) , and the existing studies assess risk factors in isolation (5,15) .…”
Section: Introductionmentioning
confidence: 99%
“…Diseases related to low BMD are multifactorial, and the associations have not yet been well established in adults. Concerning individuals’ age and sex, 3 , 4 bone metabolism is also influenced by genetics, 5 hormone replacement, use of medication, 6 , 7 sunlight exposure deficiency and vitamin D insufficiency, 8 , 9 body composition, 10 , 11 smoking, 12 alcoholism, 13 physical activities, 14 and level of formal education. 15 , 16 However, most studies have evaluated the association BMD, and these factors in older individuals isolately have not been considered in studies as well as the inter-relationship among BMD and behavioral and health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Doenças relacionadas à baixa DMO são multifatoriais, e ainda não há associações bem estabelecidas em pacientes adultos. Sobre a idade e o sexo dos indivíduos, 3 , 4 tem sido apontado que o metabolismo ósseo também é influenciado por genética, 5 reposição hormonal, uso de medicamentos, 6 , 7 deficiência de exposição à luz solar e insuficiência de vitamina D, 8 , 9 composição corporal, 10 , 11 tabagismo, 12 alcoolismo, 13 atividade física 14 e nível educacional. 15 , 16 Entretanto, a maioria dos estudos tem avaliado a associação entre DMO, e fatores associados em indivíduos mais velhos e mulheres menopausadas, essencialmente.…”
Section: Introductionunclassified
“…participants. Previous studies have indicated detrimental effect of this medication on the bone mass of adolescents and young women(34, 35). These contrasting results could be attributed to protective factors present in women from the NutriHS, who commonly practice physical activity and rarely smoke or consume alcohol.…”
mentioning
confidence: 99%
“…The follow-up of the NutriHS could explore such hypothesis.In addition to recognized factors with contribute to accumulation of bone mass during childhood and adolescenceheredity, gender, life habits, endocrinopathies, medicationsour findings support an association of BW and weight in infancy with adult bone mass, in agreement with previous studies(13, 33). A systematic review and meta-analysis demonstrated a positive association between BW and bone mass among children although weak in adults(34), concluding that BW may favor bone health in later life. On the other hand, a European birth cohort verified that prenatal growth had no significant impact in TB and LS BMD in early adulthood, but the weight gain during childhood(35).Our results are consistent since positive associations of BW quartiles occurred with several bone parameters (TB BMD, LS BMD, TB BMC and TF BMC), after several adjustments (maternal gestational weight gain, maternal pre-pregnancy BMI, breastfeeding, skin color and type of birth).…”
mentioning
confidence: 99%